IDENTIFIKASI TELUR AYAM DARI INDUK MUDA DAN TUA MENGGUNAKAN SPEKTROSKOPI INFRAMERAH DEKAT - Amalia, Riana; Trihandaru, Suryasatriya; Rondonuwu, Ferdy S (BERKALA FISIKA, 2013)
One important factor in the hatching chicken eggs industry is hatchability of the eggs. Conventionally, hatchability of the eggs is determined by the age of the hen. It is estimated thateggs which have high hatchability will produced from the hen which is aged between 25 to 55weeks. However, the age of the eggs hen is difficult to recognize from the egg itself, in particular ifthe identification needs to be done quickly and involving eggs in large quantities. This paperreports the identification of chicken egg from young and old hen using Near Infrared Spectroscopy(NIRS), followed by Principal Component Analysis (PCA). A total of 120 eggs with the amount of 60 eggs that was taken from young hen (aged around 26 weeks) and the remaining 60 eggs thatwas taken from old hen (aged arround 66 weeks) can be clearly distinguished by clusteringthrough PC1-PC2 diagram. Thus, this method can be used to identify chicken eggs based on agehen.Keywords : Chicken Eggs, NIRS, PCA.